Technologies based on energy savings for OLED devices - Mohammed Albaba; Meryem Sena Akkuş (MANAS: Journal of Engineering)
Recently, scientists are paying more attention to the Organic Light Emitting Diode (OLED) technology as it is being used in devices and displays to play videos and show photos with high resolution. This technology is used in products such as mobile phones, televisions, laptops, etc. To make the energy consumed less, new methods were shown up to prevent high energy consumption while presenting videos and photos on OLED devices and displays without losing their details and quality, one of the methods is a deep learning-based technique which is related to artificial intelligence. In this review paper, the last methods were discussed as well as their results. Saturation, brightness, contrast, and luminance are factors that impacting energy consumption. In terms of OLED mobile phones, there were a few studies that concentrated on turning off the unnecessary pixels which will be black as default, and as a result, the lifetime of batteries will be extended. Also, for OLED mobile phones, a web browser called Chameleon was presented as it has some modes to save the energy consumed while surfing the internet by remapping the displayed colors of the website.